2004
DOI: 10.1021/ja0319240
|View full text |Cite
|
Sign up to set email alerts
|

The Chirality of a Four-Way Helical Junction in RNA

Abstract: We have used a novel electrophoretic approach to determine the chirality of a four-way helical junction in RNA. From our experiments we conclude that the handedness of the helical junction in the complete ribozyme is opposite to that found in the free junction and is therefore constrained by the interaction between the unpaired loops of the ribozyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Our results indicate that a right-handed antiparallel conformation is most consistent with the FRET data. Subsequent gel electrophoresis experiments showed that this four-way junction indeed prefers the right-handed antiparallel form (30).…”
Section: Application 2: Interpreting Limited Experimental Data With Mmentioning
confidence: 96%
“…Our results indicate that a right-handed antiparallel conformation is most consistent with the FRET data. Subsequent gel electrophoresis experiments showed that this four-way junction indeed prefers the right-handed antiparallel form (30).…”
Section: Application 2: Interpreting Limited Experimental Data With Mmentioning
confidence: 96%
“…The mobility has been plotted against spacer length and fitted to a model based upon the Lumpkin–Zimm theory assuming bends of fixed angle and dihedral angle for both the A 5 bulge and the U1A box 2. ( b ) The four-way junction of the hairpin ribozyme (Goody et al 2004). The ribozyme junction was combined with an A 4 bulge with a variable length spacer of 8–22 bp between them.…”
Section: Bends and Kinks In Duplex Nucleic Acidsmentioning
confidence: 99%
“…37 Figure 9 reports the chirality values along Hammerhead ribozyme highlighting, as experimentally shown, [56][57][58] a fine regulation in the handedness of RNA junctions.…”
Section: Nucleosome and Ribosome Structuresmentioning
confidence: 81%